Submerged production and characterization of Grifola frondosa Polysaccharides : a new application tocosmeceuticals - Kim, Sang Woo (Array, 2007)
Grifola frondosa (maitake) is traditionally called 'the king of mushrooms' and 'the hen of the woods'. Both the fruiting bodies and the mycelium of maitake have been reported to have antitumor and antiviral activities. Recently, submerged culture processes have been developed, with the intention of providing opportunities for increased economic exploitation of maitake. Commonly the aim of these processes is to produce extracellular polysaccharides (EPS), mostly glucans, and to explore their applications, particularly in the cosmetic industry. A wide variety of EPS with different molecular chain length and chemical compositions are produced under different culture conditions. In this article, various biological and physicochemical properties of the EPS of G. frondosa (GF-EPS) are described, with a view to applications in the area of functional cosmeceuticals. The GF-EPS, together with GF mycelial extract (GF-MPS), showed antioxidative activity, stimulation of collagen biosynthetic activity, cell proliferation activity, and inhibitory activity of melanogenesis, without significant cytotoxicity. These diverse functionalities suggest that both GF-EPS and GF-MPS can be promising cosmetic ingredients